Relasi Manusia Dan Pengada Dalam Konsep Kalepasan Tutur Brahmokta Widhisastra - Wika Krishna, Ida Bagus; Yogiswari, Krisna S. (Jurnal Penelitian Agama Hindu, 2023)
Hindus believe in union with Brahman as the ultimate goal of life, the source of all life. The Balinese have always infused these ideas into knowledge that is considered confidential. Because readers struggle to understand and those who put it into practice require the presence of a near-perfectly competent teacher. Lack of attention to traditional Balinese texts containing metaphysical ideas and knowledge of perfection is the background of this study. This study is an attempt to describe the relationship between humans and beings from a metaphysical point of view in the form of a traditional text, the Tutur Brahmokta Widhisastra. The Tutur Brahmokta Widhisastra is one of his Siwaist-style texts that strongly expresses Kalepasan idea as one of the concepts of the relationship between humans and beings. The qualitative approach used in this study focuses on a philosophical approach that uses hermeneutic research methods to reveal the metaphysical ideas contained in Tutur Brahmokta Widisastra. Based on the critical analysis carried out, the relationship between humans and beings in Tutur Brahmokta Widisastra, the relationship between humans and beings in the human body and organs, becomes the stana of the gods and as the immovable mover of Shivaism. Kalepasan as a concept of union requires the performer to be able to understand the positions of the organs of the human body as the Sthana of the gods. In addition, people also need to understand the urips and scriptures (aksara) that represent each organ, each god. After full understanding and practice become possible, people will undoubtedly connect with beings through the path of pranayama and yoga.